2021
DOI: 10.4309/jgi.2021.47.7
|View full text |Cite
|
Sign up to set email alerts
|

The Narrative of Persons with Gambling Problems and Substance Use: A Multidimensional Analysis of the Language of Addiction

Abstract: Several studies have shown that the analysis of the narrative dimension may represent a useful instrument to shed light on certain critical psychological aspects; to this extent, it might also be fruitful to understand better the addiction disorder. The present study aimed to investigate the critical psychological-narrative aspects involved in Gambling Disorder (GD). A semi-structured interview, one which invited participants to narrate the various phases of addiction (addiction definition, onset, chronicizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Another fruitful way to analyze both the construction and alteration of self in reference to language use in conditions like ASD, SCZ and synesthesia is to investigate the narrative dimension (e.g., Giddens, 1991 ; McAdams & McLean 2013 ; Allé et al 2015 ; Adornetti and Ferretti 2021 ). This view is founded on the position that human beings construct their own identities by means of stories, e.g., by producing autobiographical narratives (Schechtman 1996 ; McAdams 2001 ; Habermas & de Silveira 2008 ; Altavilla et al 2020 ; Canali et al 2021 ). Paradigmatic of this perspective is Bruner’s constructivist model of personal identity (e.g., Bruner 2003 , 2004 ).…”
Section: The Self and Modes Of Narrationmentioning
confidence: 99%
“…Another fruitful way to analyze both the construction and alteration of self in reference to language use in conditions like ASD, SCZ and synesthesia is to investigate the narrative dimension (e.g., Giddens, 1991 ; McAdams & McLean 2013 ; Allé et al 2015 ; Adornetti and Ferretti 2021 ). This view is founded on the position that human beings construct their own identities by means of stories, e.g., by producing autobiographical narratives (Schechtman 1996 ; McAdams 2001 ; Habermas & de Silveira 2008 ; Altavilla et al 2020 ; Canali et al 2021 ). Paradigmatic of this perspective is Bruner’s constructivist model of personal identity (e.g., Bruner 2003 , 2004 ).…”
Section: The Self and Modes Of Narrationmentioning
confidence: 99%
“…In this sense, since narrative coherence is related to the ability to establish temporal and causal links between events in order to provide continuity to the narrative plot (e.g., Reese et al, 2011), the processing of temporality represents a central element for the narrative dimension (Suddendorf and Corballis, 1997;Corballis, 2011), which has been studied in other clinical populations, such as autism (Ferretti et al, 2018;Marini et al, 2019). Interestingly, as we mentioned, in both the Canali et al (2021) and Altavilla et al (2020) studies, the analysis of linguistic markers related to temporal factors, especially to selfprojection into the future, i.e., the self-referential ability to imagine oneself in personal future scenarios (Atance and O'Neill, 2001;Buckner and Carroll, 2007), revealed an absence of reference to the future, showing that people with an addictive disorder failed to integrate their experience with possible self-based future scenarios different from the addiction condition.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, out of a total of 18 studies identified in literature that explored narratives of addiction, only two studies have explicitly examined structural features in personal narratives of individuals diagnosed with an addictive disorder: one study focused on the assessment of narrative global coherence ( Canali et al, 2021 ), the other on narrative complexity and its relation to recovery ( Rowlands et al, 2021 ). As for the second variable we considered, namely agency in the framework of narrative identity, only a few studies have examined it in self-narratives of people with an addictive disorder ( Altavilla et al, 2020 ; Canali et al, 2021 ) and in recovery context ( Rowlands et al, 2019 ; see also an exploratory stud by Rowlands et al, 2020 ), while other investigations have proposed to analyze agency in autobiographical narratives in addiction using a sociological approach based on actor-network theory ( Törrönen and Tigerstedt, 2018 ; Törrönen et al, 2020 ; Törrönen, 2023 ). Finally, one study has analyzed the emotional dimension in autobiographical narratives of people with GD ( Altavilla et al, 2020 ).…”
Section: Studies On Narrative Identity In Addictionsmentioning
confidence: 99%
See 2 more Smart Citations